Benefits of forest therapy for adult mental health: a systematic review and meta-analysis based on the Profile of Mood States (POMS) - Shang, Xueyan; Lu, Jiahao; Tao, Meng; Fei, Cheng; Fei, Jiaming (Frontiers in Psychology, 2025)
ObjectiveThis study aims to assess the effects of forest therapy on human mental health through meta-analytic methods and to examine the moderating variables that influence this relationship. The goal is to provide a scientific basis for optimizing forest therapy interventions tailored to different populations to enhance mental health outcomes.MethodsDatabases such as CNKI, Wanfang, Web of Science, PubMed, Cochrane, and Embase were utilized for data collection, and data processing was performed using EndNote X9 and Stata 16.0 statistical software. The weighted mean difference (WMD) and 95% confidence interval (CI) were used as effect size indicators for the meta-analysis, and relevant moderator variables were tested.ResultsThe study analyzed three subgroups based on intervention duration, exercise intensity, and participant origin. Subgroup 1 (t ≤ 15 min), Subgroup 2 (15 min < t < 60 min), and Subgroup 3 (t ≥ 60 min) were categorized by intervention duration. Participants were further divided into Static forest therapy (Subgroup 1) and Dynamic forest therapy (Subgroup 2) based on exercise intensity. Additionally, participants were classified as either Asian (Subgroup 1) or European (Subgroup 2) based on their origin. The results indicated that longer single sessions of forest therapy were more beneficial in improving both positive and negative psychological states. Dynamic forest therapy was more effective than static forest therapy in enhancing these states. Furthermore, forest therapy was found to be more effective in improving both negative emotions (e.g., nervousness, depression, confusion) and positive emotions (e.g., vitality) in Asian populations compared to European populations.ConclusionForest therapy has been shown to effectively alleviate anxiety, anger, depression, fatigue, and confusion, while also enhancing vitality. However, when the duration of the therapy is less than one hour, its effects on reducing fatigue and enhancing vitality are less pronounced.